Penerapan Culturally Responsive Teaching untuk Mengeksplorasi Karakter Bermasyarakat pada Siswa Sekolah Dasar - Herlina, Siti; Puspita, Ari Metalin Ika; Muhimmah, Hitta Alfi (Universitas Negeri Padang, 2025)
This study was motivated by a government programme called the 7 Great Habits of Indonesian Children in Primary Schools, one of which is social skills. One way for students to understand the character values inherent in social skills is through a culturally responsive teaching approach. The concept of culturally responsive teaching can accommodate and nurture the character values of a social system. The purpose of this study is to describe the application of culturally responsive teaching in exploring community values and implementing them in elementary school students. The approach used in this study is a descriptive qualitative one, involving interviews with four teachers and observations conducted with students at SD Negeri Mulyoagung, which were analysed using a thematic approach. The results of this study indicate that the application of culturally responsive teaching in primary school learning enables both teachers and students to explore their surrounding culture and incorporate it into social values such as mutual assistance, mutual respect, tolerance, justice, equality, environmental responsibility, and joy. This is because, in its implementation, learning integrated with culturally responsive teaching enables students to interact more with their peers and environment and integrate various diversities into a harmonious whole.